Le rôle des marqueurs d’intensification dans l’expression des émotions en anglais - Lucile Bordet (Lexis: Journal in English Lexicology)
This paper investigates the link between the expression of emotions and the linguistic phenomenon known as intensification. Since intensification has an emotional and a cathartic function, it seems naturally linked with the expression of emotions. As such, intensification devices may be considered as a preferred means for speakers to convey their emotions. After delineating the theoretical framework of this study and defining intensification and its functions as well as what the term “emotion” covers in this paper, I explain the methodology used to analyze the corpus. It is composed of two video extracts from the Late Show with Conan O’Brien dealing with the death of Robin Williams. This paper offers a multimodal analysis of the expression of emotions thanks to intensification devices.